2022
DOI: 10.21037/atm-21-6285
|View full text |Cite
|
Sign up to set email alerts
|

Thoracolumbar kyphosis in postmenopausal osteoporosis patients without vertebral compression fractures

Abstract: Background: To investigate whether thoracolumbar kyphosis (TLK) of the spine is related to the reduction of bone mineral density (BMD) in postmenopausal osteoporosis women, and whether BMD of postmenopausal osteoporosis women can predict the occurrence of TLK. Methods: This retrospective cohort study included 224 postmenopausal female patients hospitalized for osteoporosis from December 2017 to December 2020, and the control group included 270 postmenopausal female patients hospitalized for thoracolumbar degen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…As the curvature of the chest or waist increases, the local bone density in pre-and postmenopausal women decreases (34). Guo et al also found that in postmenopausal patients with OP, TLK can occur even without compression fractures and that postmenopausal women are more likely to develop TLK in the future (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the curvature of the chest or waist increases, the local bone density in pre-and postmenopausal women decreases (34). Guo et al also found that in postmenopausal patients with OP, TLK can occur even without compression fractures and that postmenopausal women are more likely to develop TLK in the future (35).…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al. also found that in postmenopausal patients with OP, TLK can occur even without compression fractures and that postmenopausal women are more likely to develop TLK in the future ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a systemic skeletal disorder characterized by reduced bone mass, impaired microstructure of bone tissue and increased bone fragility and risk of fracture ( 29 , 30 ). Currently, some effective treatments are used for osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…The following data were recorded: age, sex, body mass index (BMI), American Society of Anesthesiologists (ASA) score, the position of the hernia, surgery time, blood loss, conversion, postoperative hospital stay, follow-up time, complications, and hernia recurrence. The pain scores were checked 1 day after the surgery by a member of the team using a visual analog scale (VAS) (18,19). Some patients were followed up with outpatient visits, while…”
Section: Data Collectionmentioning
confidence: 99%